2020
DOI: 10.3390/cancers12082200
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Peri-Tumoral and Intra-Tumoral Radiomic Features on Bi-Parametric MRI Accurately Stratifies Prostate Cancer Risk: A Multi-Site Study

Abstract: Background: Prostate cancer (PCa) influences its surrounding habitat, which tends to manifest as different phenotypic appearances on magnetic resonance imaging (MRI). This region surrounding the PCa lesion, or the peri-tumoral region, may encode useful information that can complement intra-tumoral information to enable better risk stratification. Purpose: To evaluate the role of peri-tumoral radiomic features on bi-parametric MRI (T2-weighted and Diffusion-weighted) to distinguish PCa risk categories as define… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
76
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(86 citation statements)
references
References 37 publications
7
76
2
1
Order By: Relevance
“…Patch-based deep learning approaches using convolutional neural networks have been used to detect and characterise prostate cancer; 17,18 however, these studies did not make use of important information in the peritumoural region, which has been shown to improve disease characterisation and classification performance. 15,16,26 Algohary and colleagues 19 showed the benefit of extracting radiomic representations from peritumoural regions along with intratumoural regions. They highlighted the differences in concentration of epithelial cells and lymphocytes between low-risk and high-risk regions by mapping the representative peritumoural regions on biparametric MRI to the whole-mount pathology slides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patch-based deep learning approaches using convolutional neural networks have been used to detect and characterise prostate cancer; 17,18 however, these studies did not make use of important information in the peritumoural region, which has been shown to improve disease characterisation and classification performance. 15,16,26 Algohary and colleagues 19 showed the benefit of extracting radiomic representations from peritumoural regions along with intratumoural regions. They highlighted the differences in concentration of epithelial cells and lymphocytes between low-risk and high-risk regions by mapping the representative peritumoural regions on biparametric MRI to the whole-mount pathology slides.…”
Section: Discussionmentioning
confidence: 99%
“…We aimed to construct an integrated nomogram (referred to as ClaD) combining deep learning-based imaging predictions, PI-RADS scoring, and clinical variables using multivariable logistic regression to identify clinically significant prostate cancer on biparametric MRI. Since previous research 19 has suggested the importance of the peritumoural region for characterisation of prostate cancer on biparametric MRI, we explored multiple input configurations of the deep learning network, with patches extracted at different scales and each subsequent scale incorporating additional information from the peritumoural region.…”
Section: Implications Of All the Available Evidencementioning
confidence: 99%
“…The 27 studies, and by extension, the CAD systems presented or evaluated within them, were categorized as either ROI Classification (ROI-C), Lesion Localization and Classification (LL&C), or Patient Classification (PAT-C); the categories are shown diagrammatically in Figure 2. ROI-C refers to (n = 16) studies where CAD systems classified pre-defined regions of interest (ROI), e.g., manually contoured lesions [19][20][21][22][23][24][25][26][27][28][29][30][31][32]44,45], LL&C refers to (n = 10) studies where CAD systems performed simultaneous lesion localization and classification [33][34][35][36][37][38][39][40][41][42], and PAT-C refers to (n = 1) studies where CAD systems classified patients directly [43].…”
Section: Literature Searchmentioning
confidence: 99%
“…All 27 included studies used a retrospective study design. The median size of patient cohorts used for evaluation was 98 (range 30 to 417, n = 26) for studies where the size of the evaluation patient cohort was reported [19][20][21][22][23][24][25][26][27][28][29][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. Most studies (n = 18) considered clinically suspected patient cohorts [20][21][22][23]27,31,[34][35][36][37][38][39][40][41][42][43][44][45], while fewer studies (n = 9) considered patient cohorts with biopsy-proven prostate cancer [19,[24][25][26]…”
Section: Patient and Study Characteristicsmentioning
confidence: 99%
“…8 Medical imaging enables a non-invasive analysis of the functional and physiological properties of tumors, and the different available modalities are increasingly recognized for containing high-dimensional mineable data, which in turn can be used to improve medical decision making. 9,10 Imaging can also help in characterizing peritumoral regions, which are not always surgically removed for molecular characterization 11,12 and may convey information related to the tumor microenvironment. 13,14 For example, imaging characteristics of tumors are increasingly being used to predict gene expression.…”
Section: Introductionmentioning
confidence: 99%